RETRACTED: First Report of Vibrio tubiashii Associated with a Massive Larval Mortality Event in a Commercial Hatchery of Scallop Argopecten purpuratus in Chile - Rojas, Rodrigo; Miranda, Claudio D.; Santander, Javier; Romero, Jaime (Frontiers in Microbiology, 2016)
The VPAP30 strain was isolated as the highly predominant bacteria from an episode of massive larval mortality occurring in a commercial culture of the Chilean scallop Argopecten purpuratus. The main aims of this study were, to characterize and identify the pathogenic strain using biochemical and molecular methods to demonstrate its pathogenic activity on scallop larvae, to characterize its pathogenic properties and to describe the chronology of this pathology. The pathogenic strain was identified as Vibrio tubiashii based on its phenotypic properties and the sequence analysis of its 16S rRNA and housekeeping genes (ftsZ, gapA, gyrB, mreB, pyrH, recA, rpoA and topA). When triplicate cultures of healthy 10–day–old scallop larvae were challenged with 1×105 colony forming units (CFU) mL-1 of the VPAP30 strain, percentages of larval survival of 78.87 ± 3.33%, 34.32 ± 4.94% and 0% were observed at 12, 24 and 36 h, respectively; whereas uninfected larval cultures showed survival rates of 97.4 ± 1.24% after of 48 h. Clinical symptoms exhibited by the scallop larvae infected with the VPAP30 strain include the accumulation of bacteria around the scallop larvae, velum disruption and necrosis of digestive gland. The 50% lethal dose (LD50) of VPAP30 strain at 24 and 48 h was 1.3×104 and 1.2×103 CFU mL-1, respectively. The invasive pathogenic activity of the VPAP30 strain was investigated with staining of the bacterial pathogen with 5-DTAF and analysing bacterial invasion using epifluorescence, and a complete bacterial dissemination inside the larvae at 24 h post-infection was observed. When scallop larvae were inoculated with cell-free extracellular products (ECPs) of VPAP30, the larval survival rate was 59.5 ± 1.66%, significantly (P<0.001) lower than the control group (97.4 ± 1.20%) whereas larvae treated with heat-treated ECPs exhibited a survival rate of 61.6 ± 1.84% after 48 h of exposure. This is the first report of the isolation of V. tubiashii from the diseased larvae of the scallop A. purpuratus, occurring in a commercial culture in Chile, and it was demonstrated that the VPAP30 strain exhibits high pathogenic activity on scallop larvae, mediated both by bacterial invasion and the production of toxigenic heat-stable compounds